Implementación de contabilidad comercial y aplicación de indicadores financieros en la empresa Max Color de la ciudad de Loja. Provincia de Loja. Período mayo – junio 2016 - Quezada Quezada, Jenny Carmen (2017)
he present thesis topic called "IMPLEMENTATION OF COMMERCIAL ACCOUNTING AND APPLICATION OF FINANCIAL INDICATORS IN THE MAX COLOR COMPANY OF THE CITY OF SHOP. PROVINCE OF SHOP. PERIOD MAY - JUNE 2016 ", was made with the purpose of providing a management instrument that allows the owner to have an efficient control of the commercial activities and to know the real economic and financial situation of the company. The work carried out allows us to fulfill the objectives set out in the respective thesis project, where it began with the presentation of the theoretical content of the commercial accounting that served as the basis for the development of the research. Then, the design of documents that allowed a correct application of the accounting system, then proceeded with the practical process starting with the initial inventory, a plan and manual of accounts, the economic transactions were recorded, then Be summarized in the general ledger to perform the balance sheet and work sheet, en then the face statements were presented, and finally the financial indicators were used to demonstrate the clear and real situation of the company. It concludes with the presentation of the Financial Statements that allowed to obtain real financial information about the company that were obtained after the application of the whole accounting process, before this it is recommended to continue with application of the accounting system since it allows a timely registration, demonstrating Through reports the economic reality of the entity.